Heterologous protein expression in pseudoalteromonas haloplanktis TAC125 - Parrilli, Ermenegilda; Tutino, Maria Luisa (Springer International Publishing, 2017)
The Antarctic strain Pseudoalteromonas haloplanktis TAC125 is considered one of the model organisms of cold-adapted bacteria, and during last years, it has been exploited as an alternative expression system for recombinant protein production. P. Haloplanktis TAC125 was the first Antarctic bacterium in which an efficient geneexpression technology was set up, and several generations of cold-adapted gene-expression vectors allow the production of recombinant proteins either by constitutive or inducible systems and to address the product toward any cell compartment or to the extracellular medium. Moreover, the development of synthetic media and efficient fermentation schemes, to upscale the recombinant protein production in automatic bioreactors, makes the industrial application of P. Haloplanktis TAC125 more achievable and concrete. The cellular physicochemical conditions and folding processes in P. Haloplanktis TAC125 are quite different from those observed in canonical mesophilic hosts and allowed the production of several difficult-to-express protein products, some of which are of human origin. The recently reported possibility to produce proteins within a range of temperature from 15 to -2.5 °C enhances the chances to improve the conformational quality and solubility of recombinant proteins. This chapter outlines main features and potentiality of this unconventional protein production platform.